2022
DOI: 10.1111/cbdd.14136
|View full text |Cite
|
Sign up to set email alerts
|

A review on computer‐aided chemogenomics and drug repositioning for rationalCOVID‐19 drug discovery

Abstract: Application of materials capable of energy harvesting to increase the efficiency and environmental adaptability is sometimes reflected in the ability of discovery of some traces in an environment-either experimentally or computationally-to enlarge practical application window. The emergence of computational methods, particularly computer-aided drug discovery (CADD), provides ample opportunities for the rapid discovery and development of unprecedented drugs.The expensive and time-consuming process of traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 163 publications
0
9
0
Order By: Relevance
“…But molecular docking as well as no dynamic study has been yet reported so far for 25-hydroxy vitamin D against SARS-CoV-2. Since SARS-CoV-1 and SARS-CoV-2 have very similar binding modes to human ACE2, 25-hydroxy vitamin D may have antiviral effects against both of these CoVs as well as any future CoVs that originate from animal reservoirs to infect humans [ 85 ]. Further in-vitro and in-vivo research into this connection is warranted [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…But molecular docking as well as no dynamic study has been yet reported so far for 25-hydroxy vitamin D against SARS-CoV-2. Since SARS-CoV-1 and SARS-CoV-2 have very similar binding modes to human ACE2, 25-hydroxy vitamin D may have antiviral effects against both of these CoVs as well as any future CoVs that originate from animal reservoirs to infect humans [ 85 ]. Further in-vitro and in-vivo research into this connection is warranted [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SARS-CoV-2 and SARS-CoV viruses hidden in various agricultural products have brought irreversible harm to human health [ 42 ], therefore it is an urgent task to find a simple solution to the identification and treatment of such viruses [ [43] , [44] , [45] , [46] ]. However, this pair of viruses belong to β-Coronavirus family with high genetic similarity.…”
Section: Introductionmentioning
confidence: 99%
“…to discover, among the ENAMINE compounds database, 7,8-diaminopelargonic acid aminotransferase inhibitors that could inhibit the growth of Mycobacterium tuberculosis strain Mtb H37Ra . During the recent pandemic, the use of in silico methods is one of the drug discovery approaches utilized to address an urgent need to find new drugs against COVID-19 and other diseases like HIV-AIDS and cancer. Our previous study also employed an in silico method as a preliminary tool to screen 14,000 small molecule inhibitors against glycosylation proteins dysregulated in cancer …”
Section: Introductionmentioning
confidence: 99%